Catalytic removal of ozone and design of an ozone converter for the bleeding air purification of aircraft cabin. (April 2017) - Wu, Fan; Wang, Mingyuan; Lu, Yuanwei; Zhang, Xingjuan; Yang, Chunxin
Abstract: Ozone is a major gaseous pollutant in the aircraft cabin environments. The objective of this study is to experimentally investigate the ozone removal capability of the catalyst palladium loading on the activated carbon fiber (Pd/ACFs) under various operating conditions. First, the effects of the activated carbon fibers on ozone removal are analyzed. The results show that the ozone removal over ACFs comes from the coupling effects of adsorption, chemical reaction and catalysis. The ozone conversion over the Pd/ACFs film is then confirmed to be effective when the temperature is higher than 90 °C. The ozone removal rate over the Pd/ACFs exceeds 98% after accelerating test with an initial concentration of 37 ppm at temperature of 150 °C for 80 h. The catalyst film Pd/ACFs can meet the flight requirement for 5000 h. Based on the one-trough test results, a honeycomb reactor filled with catalyst Pd/ACFs was designed and built. The test of the reactor performance shows that the catalyst film Pd/ACFs is a good choose for the ozone removal in the bleed air of aircraft cabin. However, the pressure drop in the self-manufactured reactor is slightly high. Therefore, it is better to optimize the configuration of the ozone converter to meet the requirement of pressure drop in the future. Highlights: The palladium loading on the activated carbon fibers (Pd/ACFs) are proposed to study the ozone removal in the aircraft cabin. The Ozone removal over ACFs is the coupling effects of adsorption, chemical reaction and catalysis. Ozone can be removed efficiently by the catalyst Pd/ACFs. The prototype ozone converter are produced and its performance is tested.